Hyperfine characterization of tin-doped indium sesquioxide - Mercader, Roberto Carlos (1985)
The hyperfine interactions at In and Sn sites of In2O3∶Sn (ITO) were measured through time-differential perturbed angular correlations and Mossbauer spectroscopy, respectively. Polycrystalline samples prepared by co-precipitation with nominal 0.025, 1 and 5 at.% Sn were studied. They all showed the cubic bixbyite structure characteristic of In2O3 after annealings at 200 °C. The quadrupole interaction at In sites appears nearly independent of Sn concentration being the main result of the presence of Sn in the lattice, the gradual disappearence of the dynamic perturbation caused by after-effects. The Mossbauer data demonstrate that Sn ions are in a 4+ state with ΔQ=0.606 mm/s andδ=0.226 mm/s relative to SnO3Ca at room temperature.